Hubungan Usia Gestasi terhadap Kejadian Asfiksia Neonatorum di RSUD Kabupaten Kediri Periode Januari s/d Juni 2017: Relationship between Gestational Age and Asphyxia Neonatorum in Kediri District Hospital for the Period January to June 2017 - Maringga, Estin Gita; Yuniasari, Nunik Ike (Universitas Muhammadiyah Sidoarjo, 2017)
Infant mortality now needs more attention from various parties, especially infant mortality caused by asphyxia neonatorum. Based on WHO data, the number of newborn deaths as many as 4 million babies as a result of asphyxia neonatorum, this condition contributes to the death rate in children under 5 years old of 38%. This study aims to determine the correlation of gestational age to the incidence of asphyxia neonatorum in Kediri Regency Hospital Period of January to June 2017. This study is an analytic study with retrospective cohort approach. This study took place in Kediri Regency Hospital. The study data were taken on 2-28 November 2017. The sample size was 62 respondents, chosen by simple random sampling technique. The independent variable is gestational age and the dependent variable is the level of asphyxia neonatorum. Dependent and independent variables were measured using data collection sheets, the data were taken from the medical record. Quantitative data analysis techniques used spearman rank test. 35 respondents who had aterm gestational age, 60% of them had moderate asphyxia, while from 24 respondents who had preterm gestational age, 83.3% of them had moderate asphyxia and 12.5% had severe asphyxia. The analysis result of Spearman Rank of IBM SPSS was 22 asymp sign (2 tailed) obtained result as α= 0.01 < 0.05. Gestational age has a significant correlation with the incidence of asphyxia neonatorum.